Evaluate the extent to which the teachers of the first cycle of basic education achieved Of TQM standards from the point of view of managers Study in AL -Hassakeh Schools (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The study aimed to assess the extent to which the teachers of the first cycle of basic education in Al-Hasakah achieved the criteria of TQM from the point of view of the principals of these schools. The researcher used a questionnaire which included the following criteria: 1. Planning and designing educational attitudes; 2. Providing, 3 - the ability to understand the scientific material and understand the nature and integration with other materials, 4 - the use of strategies and techniques of education, 5 - assessment of students and follow - up learning outcomes, 6 - cooperation with his superiors and colleagues, students and parents. The study found that the TQM standards of the teachers of the first cycle in basic education in Al-Hasakah governorate from the point of view of managers were very high for all standards except for the criterion of using the strategies and the educational techniques were achieved with a medium degree. There were statistically significant differences among the members of the research sample according to the gender variable in favor of females. There were statistically significant differences among the members of the research sample according to the variable of administrative experience for the benefit of those with experience from 1-5 years. Evaluation. In the light of previous findings, the study presented some suggestions that can be traded to improve the quality of teachers' performance in accordance with TQM standards.